KONSEP PEMBENTUKAN KARAKTER PRIBADI ANAK MENURUT PEMIKIRAN ALBERT BANDURA DAN MUHAMMAD MUTAWALLI AL-SYARAWI - Anida Magfirah (Jurnal Ilmiah Ilmu Ushuluddin, 2015)
The globalization brings many impacts in the world. In Indonesia, some people consider it as a threat for the localwisdom and national culture. In this era, the flow of information cannot be repressed, so all people can access it easily.Somehow it will be positive, but the reality said that the negative impacts is bigger for the community especially for theyoung generation. To prevent the things happen, it is needed for them to have strong character in their personality. Thiswriting discussed about the concept of building the childrens character since early. So far, the article is going to comparethe thought of Albert Bandura and Muhammad Mutawwali al-Syarawi in building character. In the end, it will beconcluded the differences and the similarities between both concepts.